Estimation of environment as a background for green pea breeding for adaptivity - V.F. Pivovarov; I.P. Kotlyar (Овощи России, 2012)
The evaluation of adaptive and producing capacity of green pea varieties for period of four years has been done. It was found that condition of experimental fields of VNIISSOK can provide the possibility for associated traits of productivity, ecological adaptivity, and their combination in the same genotype.